Struktur dan Unsur Kebahasaan Teks Deskripsi Siswa Kelas VII SMP SIMA Padang - Putri, Octa Stafia; Noveria, Ena (ALSYS, 2023)
The purpose of this study was to describe the structure and linguistic elements of the descriptive text for class VII SMP SIMA Padang. This type of research is a qualitative research with descriptive method. The data collection technique in this study is the fishing technique. The technique of validating the research data is the triangulation technique. The steps for analyzing the data are first, identifying the data. Second, analyze the data. Third, interpret the data. Fourth, conclude the results of the data. The results of this study, namely First, in writing descriptive text class VII students of SMP SIMA Padang have used all three text structures. This is evident from the 22 descriptive texts that have been analyzed, there are 14 complete descriptive texts using identification/general description, section descriptions and conclusions, 20 texts that have a section description structure, and 14 texts that have a conclusion structure. Second, from a linguistic point of view, Class VII students of SMP SIMA Padang still have errors. This is evident from the 203 sentences analyzed, there were 140 sentences and EYD which were incorrect. This can be seen from 5 errors in the incorrect pattern of sentence elements, 128 errors in the incorrect use of capital letters, 13 errors in inappropriate prepositions, 13 errors in pronouns ku-, you-, -ku, -mu. , and -nya, and 48 errors in improper punctuation.